Aisyiyah's Role In Preventing Child Marriage In Indonesia: A Qualitative Study - Enny Fitriahadi; Islamiyatur Rokhmah; Khusnul Hidayah; Ika Afifah Nugraheni; Deccy Nopiyana (Universitas Aisyiyah Yogyakarta, 2023)
The pandemic is having a negative effect on the economies of the most vulnerable households and increasing the risk of child marriage. Millions of children have been badly affected by the COVID-19 pandemic, the most affected are those who are under the socio-economic status of people who are already poor and neglected. The purpose of this study was to analyze in depth the role of Aisyiyah’s strategies to prevent child marriage during the COVID-19 pandemic in Indonesia. This research used a qualitative research type. This research was conducted in a Sub-District of Magelang Regency, Indonesia. The sampling technique used in this research were purposive sampling and snowball sampling. Sub-District Government is very concerned with the prevention of child marriage programs that have been carried out by involving cross-sectors such as Religious Affair Office (KUA), Public Health Center (Puskesmas), Village Advisory Advisor (Babinsa), Midwives, Teacher, and Community Health Workers (Kader Desa). Involving the community and using the rules and norms that have been regulated by the Ministry of Religion, they collaborate with the Religious Affairs Office in implementing these regulations. Suggestions for parents that the role of parents is very important in providing early education about reproductive health in children and adolescents.